Early and long-term results of total arch replacement with the frozen elephant trunk technique for acute type A aortic dissection. (1st April 2020) - Yoshitake, Akihiro; Tochii, Masato; Tokunaga, Chiho; Hayashi, Jun; Takazawa, Akitoshi; Yamashita, Kentaro; Chubachi, Fumiya; Hori, Yuuto; Nakajima, Hiroyuki; Iguchi, Atsushi; Gatate, Yodo; Nakano, Shintaro; et al.
Abstract: OBJECTIVES: We evaluated the operative and long-term outcomes of the frozen elephant trunk (FET) technique for acute type A aortic dissection. METHODS: This study evaluated 426 consecutive patients who underwent aortic repair for acute type A aortic dissection from June 2007 to December 2018 at our centre. Of these, 139 patients underwent total arch replacement with FET (FET group), and 287 underwent other procedures (no FET group). Ninety-two patients in the FET group were matched to 92 patients in the no FET group by using propensity score matching analysis. RESULTS: Thirty-day mortality and neurological dysfunction were not significantly different between the FET and no FET groups (1.4% vs 2.4%, P = 0.50 and 5.0% vs 6.3%, P = 0.61, respectively). Long-term survival was better in the FET group than in the no FET group ( P = 0.008). Freedom from distal thoracic reintervention was similar in the FET and no FET groups ( P = 0.74). In the propensity-matched patients, freedom from aortic-related death was better in the FET group than in the no FET group ( P = 0.044). CONCLUSIONS: Operative outcomes showed no significant difference between the 2 groups. FET contributes to better long-term survival in patients with acute type A aortic dissection.